THE CORRELATION BETWEEN EMOTIONAL INTELLIGENCE AND STUDENTS’ SPEAKING ENGLISH SKILL AT EIGHT GRADE OF SMP K BHARATA 2 JUMAPOLO THE ACADEMIC YEAR 2022/2023 - Maria Grace Sintya; Sri Handayani (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
This study aims to determine the correlation that occurs between students' emotional intelligence with the English speaking skills of eighth-grade students at SMP K Bharata 2 Jumapolo during the academic year 2022/2023. The researcher used quantitative methods as well as correlational techniques. The result of this study showed that there is a positive correlation between students' emotional intelligence and students' English speaking skills. It is proven by the results after analyzing the two variables using the Person Product Moment formula, rxy= 0.494. From the results of rx : r table = 0.494 > 0.367 and at a degree of significance of 1% rx : r table = 0.494 > 0.470. It can be concluded that the Null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. It means that there is a positive correlation between students' emotional intelligence and students' English speaking skills. Thus, the higher the students' emotional intelligence, the better their speaking skills.   Key words: Students’ Emotional Intelligence, Speaking Skill, Correlational Study.